Googling the Lifetime Risk of Stroke Around the World - Phan, Thanh G.; Haseeb, Anisha; Beare, Richard; Srikanth, Velandai; Thrift, Amanda G.; Ma, Henry (Frontiers in Neurology, 2020)
Objective: We aimed to utilise the data on lifetime risk of stroke, from Global Burden of Disease (GBD) 2016, in combination with open data platforms to create an interactive map for use by clinicians and members of the public. Further, we explore the relationship between life expectancy and life time risk of stroke. Design: Enhancing visual display of large volume of data. Setting: Published data from Global Burden of Disease (GBD) 2016 on life time risk of stroke. Participants: None Intervention: None Methods: Data were extracted from a portable document format (pdf) copy of the paper and exported into the R programming environment (version 3.4.4). These data were merged with (i) the world map boundary, (ii) open data platforms from the World Bank (life expectancy and income,) and (ii) open data from the United Nation Population Prospects 2017. Further we plotted the relationship between the life time risk of stroke and life expectancy. Outcomes: The map of the global burden of stroke shows a higher lifetime risk of stroke among high income countries than in low income countries (https://gntem3.shinyapps.io/strokeglobal/) . The greatest risk was among upper middle-income countries such as China and Eastern and Central European countries such as Latvia and Romania. The risk of stroke increased with greater life expectancy (β=0.48 ± 0.47, R2=0.38, p<0.01) Conclusion: The interactive map enables clinicians to search information about the lifetime risk of stroke interactively, and navigate by zooming in and out, while still retaining high resolution.